2019
DOI: 10.1186/s12894-019-0496-y
|View full text |Cite
|
Sign up to set email alerts
|

Pelvic plexus block to provide better anesthesia in transperineal template-guided prostate biopsy: a randomised controlled trial

Abstract: Background To evaluate the efficacy of pelvic plexus block (PPB) in relief pain during transperineal template-guided prostate biopsy (TTPB), compared with conventional periprostatic nerve block (PNB). Methods From July 2016 to August 2017, 245 patients who were performed TTPB in Clinical Medical College of Yangzhou University were recruited. The patients were randomized into three groups using a random number table. Group-1 received prostate capsule local anesthesia wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 27 publications
0
9
0
3
Order By: Relevance
“…14 Perivesical infiltration of ropivacaine targets both the postganglionic neurons in the detrusor wall and the pelvic plexus which is located at the bilateral apex of the seminal vesicles. 11 Periurethral infiltration targets the remnants of the neurovascular bundle at the apex. 14 Ropivacaine inhibits sodium ion influx in nerve fibers, 17 thereby blocking signal transmission and decreasing involuntary bladder muscle contraction.…”
Section: Local Infiltration Anesthesiamentioning
confidence: 99%
“…14 Perivesical infiltration of ropivacaine targets both the postganglionic neurons in the detrusor wall and the pelvic plexus which is located at the bilateral apex of the seminal vesicles. 11 Periurethral infiltration targets the remnants of the neurovascular bundle at the apex. 14 Ropivacaine inhibits sodium ion influx in nerve fibers, 17 thereby blocking signal transmission and decreasing involuntary bladder muscle contraction.…”
Section: Local Infiltration Anesthesiamentioning
confidence: 99%
“…There was no statistical difference for the pain control during biopsy between PPB and PNB. However, three studies ( 12 , 16 , 18 ) and one study ( 15 ) reported 40 to 50 ml and more than 50 ml prostate biopsy, respectively, and compared with PNB, PPB patients experienced less pain during biopsy ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…By removing duplicates, reviews, and articles that were not relevant to the question, 11 articles were remained. Then, after full-text screening of these articles, six articles (12,(15)(16)(17)(18)(19) were assessed for eligibility. Further evaluations and detailed analysis of the articles were shown in Figure 1.…”
Section: Eligible Studiesmentioning
confidence: 99%
See 2 more Smart Citations